Pengaruh Akuntabilitas, Transparansi Terhadap Kinerja Anggaran Pada Instansi Pemerintah Se-Kota Denpasar - Anak Agung Gede Dalem Sukawati Dewa Nata; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2023)
A number of factors that can affect budget performance include accountability, transparency and participation in budgeting. The purpose of this study was to determine the effect of accountability and transparency on financial performance in government agencies throughout the city of Denpasar. The number of samples taken were 105 respondents. The sampling technique used is purposive sampling, while the analysis technique used is descriptive statistical test, classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test, instrument test consisting of validity and reliability test, feasibility test of the model used consists of coefficient of determination (adjusted R2), F test, and statistical test (t test), and multiple linear regression analysis. The test results show that there is a positive and significant effect between accountability on budget performance in Government agencies throughout the city of Denpasar. Judging from the results of the t test, the parameter coefficient value is 0.585 with a significance level of 0.000. There is an insignificant effect between transparency on budget performance in government agencies throughout the city of Denpasar. The parameter coefficient value is 0.119 with a significance level of 0.110.